To Evaluate the Frequencies of Post- Traumatic Cerebrospinal Fluid Leak in Patients Presenting with Traumatic Brain Injury - Hameedullah, Hashim Khan, Sahar Malik, Hamza Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Traumatic brain injury is the fourth largest cause of fatal trauma worldwide. The social and economic implications of traumatic brain injuries are immense whilst the physical and mental bearing upon the patient is devastating. Objective: Objective of this study is to evaluate the frequencies of post- traumatic cerebrospinal fluid leak in patients presenting with traumatic brain injury. Methodology of the study: This study was conducted at Neuro Surgery Department of Lady Reading Hospital, Peshawar during 20/7/2020 to 20/1/2021.In the current study a total of 303 patients presenting with initial head trauma presenting within 24 hours with Glasgow coma score ≤15, patients in age between 18 to 65 years and both gender (male/female) were included in the study. All the patients were subjected for detailed history, clinical examination and radiological examination i.e. CT and MRI was done for the confirmation of brain injury. All the patients were followed till 7th post operative day for the diagnosis of Cerebrospinal fluid leak. It is clear water cerebrospinal fluid discharge diagnosed on clinical examination till 7th post-trauma day and was determined in terms of rhinorrhea or otorrhea. Results: Our study shows that among 303 patients was analyzed as 215(71%) patients were in age range 18-40 years, 88(29%) patients were in age range 41-65 years. 239(79%) patients were male and 64(21%) patients were female. More over 18(6%) patients had CSF leak while 285(94%) patients didn’t had CSF leak. Practical Implication: This study will be useful for finding the post-traumatic cerebrospinal fluid leak. Conclusion: Our study concludes that the frequencies of post-traumatic cerebrospinal fluid leak was 6% in patients presenting with traumatic brain injury. Keywords: Post-traumatic cerebrospinal fluid leak, traumatic brain injury.